Design and Implementation of a New Cuk-Based Step-Up DC–DC Converter - Hossein Gholizadeh (MDPI AG, 2021)
This study proposes a novel modified Cuk converter. The proposed converter attempts to resolve the limitations of the conventional converters, such as voltage gain limitations of a canonical Cuk converter. Therefore, the mentioned improvement has made the proposed converters more compatible for renewable energy applications. Moreover, the increase of the voltage gain in the proposed converter has not impacted the efficiency or the voltage stress of the switches, which is common in other voltage boosting techniques, such as cascading methods. Furthermore, the advantages of a Cuk converter, such as continuity of the input current, have been maintained. The average voltage/current stresses of the semiconductor devices and various types of power losses have been calculated and compared with the existing topologies. Moreover, the non-ideal voltage gain of the proposed converters was compared with the other high step-up topologies. Eventually, the simulation results with PLECS, along with the experiments on an 120 W prototype, have been presented for validation.